Pushing the Max Planck YouTube Channel With the Help of Influencers - Donhauser, Dominik; Beck, Christina (Frontiers in Communication, 2021)
We wanted to increase the number of subscriptions to the Max Planck YouTube Channel with the help of influencers. In recent years, we have published a video series called "Max Planck Cinema” to increase students’ interest in complex scientific content. The videos generated sometimes well over 100,000 views (aggregated over several years). But these figures fall far short of the number of views of German YouTube influencers in the field of science, whose videos range from several 100,000 views to over a million. Against this background, the Max Planck Society (MPG) in 2020 launched a video series in collaboration with two YouTube influencers. The new "WISSEN WAS" video series focuses on current topics and their underlying scientific facts. Although the “WISSEN WAS” videos have been online for only a relatively short time, it can be seen that the videos produced with the influencers have significantly increased the number of subscriptions. The evaluation also shows that high numbers of views do not necessarily go hand in hand with more subscriptions as other studies have previously assumed. While the basic videos of the Max Planck Cinema series prove to be real long runners, which students regularly (year by year) search for and find on YouTube (Germany) as well as Google (Germany), thereby continuously generating views, it is currently not yet possible to estimate whether the "WISSEN WAS" videos, will still generate as high a number of views per day after several years.